The United States-Argentina honey case and the case against antidumping laws - Luzi, Nora C. (2004)
The failure of the Fifth Ministerial Conference in Cancun2 was not only a setback for the Doha Round, but also for the World Trade Organization’s efforts to enhance international trade as means to growth and development. The group of developing countries led by Brazil, China, India and South Africa, known as G-22, made the first step towards a new balance in the multilateral trading system. Agriculture was considered a key issue if the new Round was meant to succeed. (Párrafo extraído del texto a modo de resumen)